Clinical Benefit of Treatment of Stage-1, Low-Risk Hypertension: Korean National Health Insurance Database Analysis. Issue 6 (December 2018) - Lee, Chan Joo; Ryu, Jiin; Kim, Hyeon-Chang; Ryu, Dong-Ryeol; Ihm, Sang-Hyun; Kim, Yong-Jin; Shin, Jin-Ho; Pyun, Wook Bum; Kang, Hyoung-Soo; Park, Jong-Heon; Hwang, Jinseub; Park, Sungha
Abstract : Evidence about the benefits of treating uncomplicated, low-risk, stage-1 hypertension is lacking. The study aimed to investigate the association between mean blood pressure (BP) and clinical outcomes, and to determine optimal BPs in treated, low-risk, stage-1 hypertension. From the National Health Insurance Service Health Examination Database, patients with stage-1 hypertension between 2005 and 2006 were selected. They had a systolic BP of 140 to 159 mm Hg or diastolic BP of 90 to 99 mm Hg. Patients were grouped as controlled (mean BP <140/90 mm Hg; n=99 301) and uncontrolled (mean BP ≥140/90 mm Hg; n=49 460) according to their mean BP recorded during the follow-up health examination. All-cause mortality and cardiovascular outcomes were examined. Mean BPs in the controlled and uncontrolled groups were 131.1/80.9 and 144.6/86.8 mm Hg, respectively. Controlled BP was associated with significantly lower risks of all-cause mortality, all stroke, hemorrhagic stroke, ischemic stroke, and end-stage renal disease. Subgroup analysis demonstrated benefits of controlled BP in hypertensive patients aged <50 years for all-cause mortality, all stroke, hemorrhagic stroke, ischemic stroke, and end-stage renal disease, with no significant interaction according to age. The BP associated with the lowest risk of all-cause mortality was 120 to <130 mm Hg (systolic BP) and 70 to <80 mm Hg (diastolic BP). There was an increased risk of myocardial infarction in patients with mean systolic BP <120 mm Hg and diastolic BP <80 mm Hg. BP <140/90 mm Hg was associated with a significant reduction in the risk of mortality, stroke, and end-stage renal disease, with the lowest mortality risk at BP ranges of 120 to <130 and 70 to <80 mm Hg. Abstract : Supplemental Digital Content is available in the text.